The Influence of Anterior Cruciate Ligament Remnant on Postoperative Clinical Results in Patients with Remnant Preserving Anterior Cruciate Ligament Reconstruction - Andonovski, Alan; Topuzovska, Sonja; Samardjiski, Milan; Bozhinovski, Zoran; Andonovska, Biljana; Temelkovski, Zlatko (Scientific Foundation Spiroski (publications), 2017)
BACKGROUND:Anterior Cruciate Ligament (ACL) remnants have important biomechanical, vascular and proprioceptive function.AIM:To determine the influence of the ACL residual remnants after partial and complete ACL ruptures on postoperative clinical results in patients with remnant preserving ACL reconstruction. PATIENTS AND METHODS:The studyincluded66 patients divided into two groups. In patients from the investigationgroupremnant preserving ACL reconstructionwas performed, in patients from the control group single bundle ACL reconstruction was performed. The results were assessed by Rolimeter measurements, Lysholm and Tegner scores and proprioception evaluation. RESULTS:The mean side-to-side difference of anterior tibia displacement(mm)was improved from 4.4± 1.06 to 0.4± 0.7in the investigation group, andfrom 4.6 ±0.68 to 1.9± 0.64 in the controlgroup (p < 0.001).Difference in the angles in which the knee was placed by the device and the patient has improved from 1.5 ± 0.96° to 0.5 ± 0.53° in theinvestigation group and from 1.8 ± 0.78° to 1.3 ± 0.97° in the control group (p <0.05). Tegner and Lysholm scores showed no difference between the groups.CONCLUSION:Preservation of the ACL residual bundle provides a better knee stability and proprioceptive function.IntroductionArthroscopic reconstruction of the anterior cruciate ligament (ACL) is one of the most commonly performed procedures in orthopedic surgery. Although there is an improvement in surgical techniques there is still graft failure rate of 3% to 12% of the cases [1]. The main factors which have influence on the results after ACL reconstructionscan be separated into two groups: biomechanical and biological [2]. According to the studies [3]in 50 % of the patients with ACL injury, arthroscopic examination carried out prior to ACL reconstruction reveals the presence of ACL residual remnants. In patients with complete ACL rupture these remnants have non anatomic femoral insertion on the intercondylar notch or posterior cruciate ligament (PCL). Sometimes a partial rupture of the anteromedial (AM) or posterolateral (PL) bundle of the ACL canbe observed. In their article [4]Kazusa et al. gave the most detailed classification of the ACL residual remnants. Recently, the importance of the ACL remnant has been recognized in terms of its biomechanical, vascular and proprioceptive functions. The ACL remnantsattached to the lateral wall of the intercondylar notchcontribute to anteroposterior knee
Keywords: Anterior cruciate ligament rupture; Remnant preserving ACL reconstruction; Single bundle ACL reconstruction; Clinical results